Nanoparticles increase the efficacy of cancer chemopreventive agents in cells exposed to cigarette smoke condensate - Pulliero, Alessandra; Wu, Yun; Fenoglio, Daniela; Parodi, Alessia; Romani, Massimo; Soares, Christiane Pienna [UNESP]; Filaci, Gilberto; Lee, James L.; Sinkam, Patrick Nana; Izzotti, Alberto (Oxford Univ Press, 2015)
Lung cancer is a leading cause of death in developed countries. Although smoking cessation is a primary strategy for preventing lung cancer, former smokers remain at high risk of cancer. Accordingly, there is a need to increase the efficacy of lung cancer prevention. Poor bioavailability is the main factor limiting the efficacy of chemopreventive agents. The aim of this study was to increase the efficacy of cancer chemopreventive agents by using lipid nanoparticles (NPs) as a carrier. This study evaluated the ability of lipid NPs to modify the pharmacodynamics of chemopreventive agents including N-acetyl-L-cysteine, phenethyl isothiocyanate and resveratrol (RES). The chemopreventive efficacy of these drugs was determined by evaluating their abilities to counteract cytotoxic damage (DNA fragmentation) induced by cigarette smoke condensate (CSC) and to activate protective apoptosis (annexin-V cytofluorimetric staining) in bronchial epithelial cells both in vitro and in ex vivo experiment in mice. NPs decreased the toxicity of RES and increased its ability to counteract CSC cytotoxicity. NPs significantly increased the ability of phenethyl isothiocyanate to attenuate CSC-induced DNA fragmentation at the highest tested dose. In contrast, this potentiating effect was observed at all tested doses of RES, NPs dramatically increasing RES-induced apoptosis in CSC-treated cells. These results provide evidence that NPs are highly effective at increasing the efficacy of lipophilic drugs (RES) but are not effective towards hydrophilic agents (N-acetyl-L-cysteine), which already possess remarkable bioavailability. Intermediate effects were observed for phenethyl isothiocyanate. These findings are relevant to the identification of cancer chemopreventive agents that would benefit from lipid NP delivery.